Transport Infrastructure of Oil and Gas Complex - Anikin, Igor; Lapteva, Svetlana; Kozlov, Anatoliy; Kormin, Alexis (International Journal of Psychosocial Rehabilitation, 2020)
Transportation infrastructure is a rather sufficient part of economic development for any country urban, suburban or even rural area. Thus, one of the main aims of the government and local authorities is to intensify all types of logistic connection and transport for the economic growth of the country on the base of globalization processes. So, a lot of new theoretical and practical activities related to the development of transport infrastructure are increasingly becoming objects of research. Transport is one of the key issues of every country economic growth and, on the other hand, transport reflects economic activity. There are therefore problems related to assessing the efficiency of transport infrastructure and the relationship between transport infrastructure and economic growth in the region’s oil and gas industry. The main window of opportunities in the area of transport infrastructure enhancement can be opened only after working out the special measures for successful solution of the so-called public life problems. Practical realization of the presented measures for the optimization of transport infrastructure of oil and gas complex of Siberian Federal district will form an opportunity for the improvement of regulation of relations, activation of transport flows and services, in addition, the integration conditions are provided for oil and gas complex at the spatial level.